2017
DOI: 10.15252/embj.201694561
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis RETINOBLASTOMA RELATED directly regulates DNA damage responses through functions beyond cell cycle control

Abstract: The rapidly proliferating cells in plant meristems must be protected from genome damage. Here, we show that the regulatory role of the Arabidopsis RETINOBLASTOMA RELATED (RBR) in cell proliferation can be separated from a novel function in safeguarding genome integrity. Upon DNA damage, RBR and its binding partner E2FA are recruited to heterochromatic γH2AX‐labelled DNA damage foci in an ATM‐ and ATR‐dependent manner. These γH2AX‐labelled DNA lesions are more dispersedly occupied by the conserved repair prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(151 citation statements)
references
References 84 publications
(158 reference statements)
5
145
0
Order By: Relevance
“…Although auxin by itself can lead to root phenotypic changes via cell signaling, environmental factors such as radiation, heavy metals or dehydration may result in cell death or DNA damage, thus plants need to efficiently respond to these cues to adapt and avoid accumulation of potentially harmful mutations, which occur through the socalled 'DNA damage response' (DDR) pathway (Ciccia and Elledge, 2010;Hu et al, 2016). Several Arabidopsis components involved in DNA damage repair or recovery of tissue via cell regeneration have been identified, including ATAXIA TELANGIECTASIA MUTATED (ATM), ATM-RAD3-RELATED (ATR), the heterodimeric transcription factor complex ERF115-PAT1, RETINOBLASTOMA RELATED (RBR), WEE1, METHYL METANESULFONATE SENSITIVITY GENE 21 (MMS21), DNA POLIMERASE k (POL k), MERIS-TEM DESORGANIZATION 1 (MDO1) and Poly(ADP-ribose) glycohydrolase (PARG; De Schutter et al, 2007;Hashimura and Ueguchi, 2011;Heyman et al, 2013Heyman et al, , 2016Roy et al, 2013;Xu et al, 2013;Zhang et al, 2015Zhang et al, , 2016Horvath et al, 2017). Moreover, the inability to correctly replicate or repair the DNA results in cell death of stem cells, as seen in seedlings lacking functional JIN HE SHENG 1 (JHS1), a homolog of human and yeast DNA Replication Helicase/ Nuclease 2, and TOPOISOMERASE 1 (TOP1; Jia et al, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although auxin by itself can lead to root phenotypic changes via cell signaling, environmental factors such as radiation, heavy metals or dehydration may result in cell death or DNA damage, thus plants need to efficiently respond to these cues to adapt and avoid accumulation of potentially harmful mutations, which occur through the socalled 'DNA damage response' (DDR) pathway (Ciccia and Elledge, 2010;Hu et al, 2016). Several Arabidopsis components involved in DNA damage repair or recovery of tissue via cell regeneration have been identified, including ATAXIA TELANGIECTASIA MUTATED (ATM), ATM-RAD3-RELATED (ATR), the heterodimeric transcription factor complex ERF115-PAT1, RETINOBLASTOMA RELATED (RBR), WEE1, METHYL METANESULFONATE SENSITIVITY GENE 21 (MMS21), DNA POLIMERASE k (POL k), MERIS-TEM DESORGANIZATION 1 (MDO1) and Poly(ADP-ribose) glycohydrolase (PARG; De Schutter et al, 2007;Hashimura and Ueguchi, 2011;Heyman et al, 2013Heyman et al, , 2016Roy et al, 2013;Xu et al, 2013;Zhang et al, 2015Zhang et al, , 2016Horvath et al, 2017). Moreover, the inability to correctly replicate or repair the DNA results in cell death of stem cells, as seen in seedlings lacking functional JIN HE SHENG 1 (JHS1), a homolog of human and yeast DNA Replication Helicase/ Nuclease 2, and TOPOISOMERASE 1 (TOP1; Jia et al, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two independent research groups demonstrated that RBR1 directly regulates DNA repair (55,56). The rbr1 mutant is hypersensitive to DNA-damaging agents.…”
Section: Loss Of E2f Function Suppresses the Sni1mentioning
confidence: 99%
“…For example, the growth of cycb1;1 and rad51 mutants is compromised in response to cisplatin, a DNA cross linker and DSB-inducer (Weimer et al, 2016a). Similarly, brca1 mutants show enhanced cell death to Mitomycin C, a DNA cross linker (Horvath et al, 2017). DNA damage-induced hypersensitivity was also observed for mutants in PARP1,2 (Song et al, 2015) and RAD17 (Heitzeberg et al, 2004) in response to bleomycin and Mitomycin C; these genes are also damage-induced by SOG1 (Culligan et al, 2006), with a function in an alternative, microhomology-mediated nonhomologous end-joining repair pathway, and in ssDNA-sensing for checkpoint control, respectively (Shrivastav et al, 2008;Hu et al, 2016).…”
Section: Sog1 Is Required For Cell Cycle Arrest Immediately After Irmentioning
confidence: 99%
“…IR-induced SOG1 also transcriptionally activates DNA repair genes, including BRCA1 and RAD51 (Yoshiyama et al, 2009), which function in homologous recombination (HR)-based repair in S and G2 phase during normal growth (Shrivastav et al, 2008;Menges et al, 2003). SOG1 appears to mediate (via upregulated CYCB1;1, in complex with CDKB1) damage-localized HR repair by BRCA1 and RAD51, in conjunction with RBR1 (Biedermann et al, 2017;Weimer et al, 2016a;Horvath et al, 2017). HR repair can help to restore a damaged cell's genomic integrity in addition to the faster (Mao et al, 2008), predominating canonical nonhomologous end-joining repair pathway (Čermák et al, 2017).…”
mentioning
confidence: 99%